Development of a whole blood intracellular cytokine staining assay for mapping CD4(+) and CD8(+) T-cell responses across the HIV-1 genome - Meddows-Taylor, Stephen (2007)
A whole blood peptide mapping intracellular cytokine staining (ICS) assay was developed that allows the direct comparison, at the individual peptide level, of CD4(+) and CD8(+) T-cell responses that span every encoded protein, in patients infected with HIV-1. Whole blood samples from HIV-1 infected patients were stimulated with overlapping synthetic peptides spanning nine subtype C HIV-1 gene regions (Gag, Pol, Nef, Env, Tat, Rev, Vif, Vpu, Vpr). Following stimulation and permeabilization, cells were stained with fluorochrome labelled antibodies to CD3, CD8 (CD4(+) cells were defined as CD8 negative cells), and IL-2 and IFN-γ. A total of 396 overlapping peptides were arranged in pools with a matrix design which allowed the identification of individual peptide responses from multiple pool responses. HIV-1 infected patients screened using this method showed a broad range of peptide responses across the entire HIV-1 genome with CD8 T-cell responses being higher in frequency in magnitude than CD4(+) T-cell responses. The advantages of this whole blood ICS assay include the following: (1) the response to all potential HIV-1 epitopes across the genome can be examined, (2) the responding cell type can be monitored in the same reaction, and (3) considerably less blood is required than would be necessary if peripheral blood mononuclear cells (PBMC) were first isolated prior to peptide stimulation.